Development and pilot testing of PROACTIVE: A pediatric onco‐critical care capacity and quality assessment tool for resource‐limited settings - Anita V. Arias; Firas M. Sakaan; Maria Puerto‐Torres; Zebin Al Zebin; Parthasarathi Bhattacharyya; Adolfo Cardenas; Sanjeeva Gunasekera; Joyce Kambugu; Kirill Kirgizov; Jaime Libes; Angelica Martinez; Nune V. Matinyan; et al. (Cancer Medicine, 2023)
Abstract Background Nearly 90% children with cancer reside in low‐ and middle‐income countries, which face multiple challenges delivering high‐quality pediatric onco‐critical care (POCC). We recently identified POCC quality and capacity indicators for PROACTIVE (PediatRic Oncology cApaCity assessment Tool for IntensiVe carE), a tool that evaluates strengths and limitations in POCC services. This study describes pilot testing of PROACTIVE, development of center‐specific reports, and identification of common POCC challenges. Methods The original 119 consensus‐derived PROACTIVE indicators were converted into 182 questions divided between 2 electronic surveys for intensivists and oncologists managing critically ill pediatric cancer patients. Alpha‐testing was conducted to confirm face‐validity with four pediatric intensivists. Eleven centers representing diverse geographic regions, income levels, and POCC services conducted beta‐testing to evaluate usability, feasibility, and applicability of PROACTIVE. Centers' responses were scored and indicators with mean scores ≤75% in availability/performance were classified as common POCC challenges. Results Alpha‐testing ensured face‐validity and beta‐testing demonstrated feasibility and usability of PROACTIVE (October 2020–June 2021). Twenty‐two surveys (response rate 99.4%) were used to develop center‐specific reports. Adjustments to PROACTIVE were made based on focus group feedback and surveys, resulting in 200 questions. Aggregated data across centers identified common POCC challenges: (1) lack of pediatric intensivists, (2) absence of abstinence and withdrawal symptoms monitoring, (3) shortage of supportive care resources, and (4) limited POCC training for physicians and nurses. Conclusions PROACTIVE is a feasible and contextually appropriate tool to help clinicians and organizations identify challenges in POCC services across a wide range of resource‐levels. Widespread use of PROACTIVE can help prioritize and develop tailored interventions to strengthen POCC services and outcomes globally.